Diamagnetic susceptibility: An indicator of pressure induced donor localization in a double quantum well. (April 2016) - Vignesh, G.; Nithiananthi, P.
Abstract: The influence of pressure along the growth axis on carrier localization in GaAs/Al0.3 Ga0.7 As Double Quantum Well (DQW) is studied under strongly coupled regime and isolated regimes of the well. The effective mass approximation combined with variation technique is adopted with the inclusion of mismatches in effective mass and dielectric constants of the well and barrier material. Effect of the barrier and well on carrier localization is investigated by observing the diamagnetic susceptibility (χdia ) for various impurity locations (zi ) and the critical limit of the barrier (Lb ≈ 50 Å) for tunneling has also been estimated. The effect of Γ-Χ crossover due to the application of pressure on the donor localization is picturized through diamagnetic susceptibility. Highlights: The effect of Γ-Χ crossover is significant for on-center impurities. Γ-Χ crossover transforms DQW structure into DBQW structure (P > 33.2 kbar). χdia demonstrates tunnelling effects. The edge located impurities are the indicators of phase transitions. Spatial extension of carrier-donor can be experimentally studied using χdia .